Growth mechanism and electronic and magnetic properties of AgnTi alloy clusters. (January 2021) - Lai, Li; Die, Dong; Zheng, Ben-Xia; Du, Quan
Abstract: The growth behavior and electronic and magnetic properties of Agn Ti (n = 1–16) clusters have been studied by using density functional theory and unbiased structure prediction method. Geometry optimizations indicate that a Ti atom in low-energy Agn Ti cluster occupies the highest coordination position. The growth of the ground state structure shows an obvious regularity. The infrared, Raman and photoelectron spectra of Agn Ti isomers have been simulated and can be used for their structural identification in the future. The Agn Ti clusters with 19 and 17 valence electrons are respectively the easiest to lose and obtain one electron. The stability and chemical activity of the most stable structures have been analyzed by means of the averaged binding energy, dissociation energy and the gap of energy level. It is found that the Ag14 Ti cluster has greater stability and large energy gap and can be regarded as a superatom. Silver-titanium cluster as a CO adsorption material must have very small size or the concentration of Ti atoms must reach a certain value. The calculation of magnetic moment and charge distribution shows that the magnetic moment of Ti atom in Agn Ti cluster increases almost completely for n = 1–8, and significantly decreases or quenches for n = 9–16. The charge transfer between Ti and Ag atoms is the main reason for the change of magnetic moment of Ti atom. Highlights: The growth of the ground state Agn Ti cluster shows an obvious regularity. Agn Ti clusters with 19 and 17 valence electrons are the easiest to lose and obtain one electron. Magic Ag14 Ti cluster with a large energy gap can be considered a superatom. The change of magnetic moment is closely related to charge transfer.